Motives for the Emigration of Egyptian Scientists. (4th August 2014) - Saleh, Saneya
Abstract : The main interest of this study is the implication of professional emigration as a social phenomenon for the future of Egypt. Why do some of Egypt's scientists wish to emigrate? What are the factors that push them out of the country, and the forces that pull them to the countries of their destination? The chief task here is not merely to reveal their present motives, but to show this decision as a culmination of personal experience over the years, and to explain how present feelings have developed. The following material deals with the world view of Egyptian scientists who wish to emigrate. It depicts their view of their emotional state, conflicts, motives, and the successive phases they passed through upon returning to Egypt with their degrees. Expectations and views of their future in the country of their destination are also presented.